Global scaling as a logic of multinationalization - Reuber, A. Rebecca; Tippmann, Esther; Monaghan, Sinéad (Journal of International Business Studies, 2021)
Global scaling – defined as a logic of multinationalization that seeks rapid growth through the replication of a global business model across foreign markets – is an increasingly visible real-world phenomenon; however, it is one which has not yet been theorized in international business research. The purpose of this editorial is to initiate a dialogue that will lead to greater discussion and research in this area. We present the theoretical facets of the global scaling logic and compare global scaling with other conceptualizations of rapid international growth. We then draw on previous research in international business and entrepreneurship to suggest facilitators of global scaling. Finally, we highlight the challenges of global scaling and areas for future empirical research to help us better understand which kinds of firms are likely to follow a global scaling logic, and which factors contribute to its successful implementation. Throughout the discussion, we use published case studies as examples, in order to provide suggestions for teaching material on global scaling.